FROM SUFFERING TO SPECTACLE: A CRITICAL READING OF MEDIA TROPES IN MALAYALAM SHORT STORIES - S. Jayan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article explores the representation and critique of media culture in contemporary Malayalam short stories, focusing on works by Santhosh Echikkanam, Subhash Chandran, Ambikasuthan Mangad and Chandramathi. These stories dissect how the pervasive influence of television, reality shows, advertising, and news media infiltrates personal lives, distorts emotional responses, and commodifies human suffering. Through a close reading of stories like Komala, Varthashareeram, America, Commercial Break and others, the paper examines how media spectacle, consumerism, and the illusion of fame shape identities and relationships within Kerala’s socio-cultural context. The stories critique a society increasingly driven by visual culture, where reality is often filtered through artificial narratives and mediated performances. The article highlights how literature reflects and resists the erosion of empathy and authenticity in a media-saturated world.